Description of the Level of Dental Anxiety Regarding Dental Treatment in Child Patients Aged 8-10 Years at the Shine Dental Care Clinic, Makassar City - Alfah, Siti; Hadriyanti, Hadriyanti; Feblina, Ayu Rahayu; Saleh, Muh; Magfirah, Febi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Dental and oral health in children needs attention because children tend to have the impression of being afraid of dental care procedures. Anxiety about dental care procedures can result in children being uncooperative and delaying or delaying children from visiting the dentist regularly. This anxiety can be influenced by individual factors of the child patient, factors outside the individual. If anxiety is not handled properly it will cause the child to have anxiety that will continue until the next treatment or until adulthood. This research is a descriptive study using survey, observation and observation methods and is presented in tabular form which was carried out on children at the Shine Dental Care Clinic in Makassar City in September 2023. The population is the total number of patients who visited the clinic and the number of pediatric patients aged 8-10 years old who will undergo dental treatment, while the sample was taken using the positive sampling technique and the Slovin formula so that 28 respondents were obtained. The results of this study show that dental anxiety on a very anxious scale is most often found in children aged 8 years (54.5%) compared to those aged 9 years and 10 years. Based on gender, dental anxiety on the very anxious scale was more common in girls (32.3%) than boys (27.7%). Most dental procedures can cause anxiety in children aged 8-10 years. The conclusion is that dental anxiety on a very anxious scale is found to be more common in younger children than older children and girls experience more dental anxiety on a very anxious scale than boys.